lern.medien.werk.statt Hochschullernwerkstätten in der Digitalität - Holub, Barbara; Himpsl-Gutermann, Klaus; Mittlböck, Katharina; Musilek-Hofer, Monika; Varelija-Gerber, Andrea; Grünberger, Nina (Lernen und Studieren in Lernwerkstätten, 2021)
"The volume ""lern.medien.werk.statt"" is dedicated to the discussion of university learning workshops about their different concepts and their different self-image. In addition, the focus is explicitly on the topic of university learning workshops and digitality. Theoretical and conceptual connections between the discourses on learning workshops and media education will be explored, as well as possible incompatibilities, in an attempt to answer the following questions: - How can digital media be systematically integrated as tools to support free experimentation in learning workshops? - How can media education and in particular the use of digital media be meaningfully integrated into learning workshop concepts? - How does the work with (digital) media in the learning workshop practice take shape in concrete terms? The series "" Lernen und Studieren in Lernwerkstätten - Impulse für Theorie und Praxis"" is edited by Barbara Müller-Naendrup, Hartmut Wedekind, Markus Peschel and Eva Franz. The editors Barbara Holub, Klaus Himpsl-Gutermann, Monika Musilek-Hofer, Andrea Varelija-Gerber, Nina Grünberger work at the Institute for Interdisciplinary Education (IBS) at the Vienna University of Teacher Education. Katharina Mittlböck (formerly also PH Vienna) works at the University of Innsbruck. "